Wear-resistant non-slip material and method for producing same

CN122917432APending Publication Date: 2026-10-16ANTA (CHINA) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611391943.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]本申请的一个目的在于提供一种耐磨止滑材料及其制备方法,其旨在解决现有材料中的功能颗粒与聚合物基体之间的界面结合不足,功能颗粒容易在使用过程中松动或脱落,导致耐磨性能和止滑性能难以兼顾的技术问题

Benefits of technology

[0023] The beneficial effects of the second aspect described above can be referred to in the first aspect or any possible implementation of the first aspect, and will not be elaborated here. Based on the implementations provided in the above aspects, this application can also be further combined to provide more implementations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917432A_ABST
    Figure CN122917432A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of high polymer composite materials, and discloses a wear-resistant and slip-resistant material and a preparation method thereof. The wear-resistant and slip-resistant material comprises a polymer matrix and a plurality of functional units dispersed in the polymer matrix. The functional units are in an island-in-sea structure, and comprise a sea phase and an island phase dispersed in the sea phase. The island phase comprises silicon dioxide particles, silicone particles and hydroxyl-terminated polydimethylsiloxane, and the sea phase comprises siloxyl-functionalized SEBS, double-end group-functionalized solution styrene-butadiene rubber and EVA. The wear volume of the island phase is smaller than that of the sea phase and the polymer matrix, and the dynamic friction coefficient of the sea phase is greater than that of the island phase and the polymer matrix. During preparation, an island phase premix is first formed, then the functional units are prepared through melt blending and granulation, and then the functional units are dispersed in the polymer matrix. The island phase mainly provides wear resistance, and the sea phase mainly provides slip resistance, load bearing and interface transition, so that the possibility of wear-resistant particles loosening or falling off is reduced, and the material has both wear resistance and slip resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of polymer composite materials technology, and in particular to a wear-resistant and anti-slip material and its preparation method. Background Technology

[0002] Materials that come into contact with surfaces, such as shoe soles, tires, and floor mats, typically need to possess both good abrasion resistance and slip resistance. Take foamed shoe sole materials as an example: they are lightweight, soft, elastic, and offer good cushioning. However, they are prone to wear during prolonged use and require sufficient friction on dry, wet, or liquid surfaces. Yet, achieving both abrasion resistance and slip resistance is often difficult. For instance, while adding hard abrasion-resistant particles or lubricating abrasion-resistant components can improve abrasion resistance, it may reduce the material's surface flexibility, effective contact area, or coefficient of friction. Conversely, increasing the material's surface adhesion or deformation capacity, while improving slip resistance, may accelerate material wear. Summary of the Invention

[0003] One objective of this application is to provide a wear-resistant and anti-slip material and its preparation method, which aims to solve the technical problem that the interfacial bonding between functional particles and polymer matrix in existing materials is insufficient, and the functional particles are prone to loosening or falling off during use, making it difficult to achieve both wear resistance and anti-slip performance.

[0004] To achieve the above objectives, in a first aspect, this application provides a wear-resistant and anti-slip material, comprising a polymer matrix and a plurality of functional units dispersed in the polymer matrix; the functional units have an island structure and include a marine phase and an island phase dispersed in the marine phase; the wear volume of the island phase is smaller than the wear volume of the marine phase and the polymer matrix, and the dynamic friction coefficient of the marine phase is greater than the dynamic friction coefficient of the island phase and the polymer matrix.

[0005] This application disperses functional units within a polymer matrix, each containing both marine and island phases. The wear volume of the island phase is smaller than that of the marine phase and the polymer matrix, thus enabling the island phase to withstand wear loads generated during material use and reducing direct wear on the functional units and the polymer matrix. The marine phase has a higher coefficient of dynamic friction than the island phase and the polymer matrix, increasing friction between the functional units and the contact surfaces. Therefore, the functional units, through the island and marine phases respectively, provide wear resistance and anti-slip properties, allowing the functional units dispersed within the polymer matrix to simultaneously possess both wear-resistant and anti-slip properties.

[0006] Meanwhile, since the island phase is dispersed within the marine phase, the marine phase can, to some extent, serve as a buffer zone and interfacial transition zone between the island phase and the polymer matrix. When the material is subjected to friction, compression, or bending, the marine phase can buffer the stress caused by the performance differences between the island phase and the polymer matrix through its own deformation, reducing the direct stress concentration at the interface between the island phase and the polymer matrix. Compared to directly incorporating wear-resistant components into the polymer matrix, this island structure reduces the possibility of the island phase loosening or detaching from the polymer matrix during repeated wear, thus maintaining the wear-resistant properties of the island phase and the anti-slip properties of the marine phase, thereby achieving a balance between the material's wear resistance and anti-slip performance.

[0007] In conjunction with the first aspect, according to one embodiment of this application, the island phase includes an island phase matrix and a first wear-resistant particle group and a second wear-resistant particle group distributed in the island phase matrix. The first wear-resistant particle group includes a plurality of first wear-resistant particles, and the second wear-resistant particle group includes a plurality of second wear-resistant particles. The first wear-resistant particles and the second wear-resistant particles belong to different size levels, and the wear volume of both the first wear-resistant particles and the second wear-resistant particles is smaller than the wear volume of the island phase and the polymer matrix.

[0008] The first and second wear-resistant particle groups each comprise multiple wear-resistant particles belonging to different size levels, creating a multi-sized wear-resistant structure within the island phase. Wear-resistant particles of different size levels can withstand wear at different spatial scales. Larger wear-resistant particles form a wear-resistant support framework, while smaller particles are distributed among the larger particles, thus increasing the number of particles in the island phase capable of bearing wear loads. Both the first and second wear-resistant particles have a smaller wear volume than the marine phase and the polymer matrix, allowing them to jointly bear the wear load applied to the island phase and reduce material loss due to continuous friction.

[0009] In conjunction with the first aspect, according to one embodiment of this application, the first wear-resistant particle is a nano-sized particle, and the second wear-resistant particle is a micron-sized particle; and / or, the average particle size of the first wear-resistant particle is 10 to 100 nm; and / or, the average particle size of the second wear-resistant particle is 5 to 10 μm.

[0010] In conjunction with the first aspect, according to one embodiment of this application, the first wear-resistant particle comprises nano-silica; and / or, the second wear-resistant particle comprises silicone microspheres; and / or, the island phase matrix is ​​hydroxyl-terminated polydimethylsiloxane; and / or, at least one of the first wear-resistant particle and the second wear-resistant particle is a spherical particle.

[0011] In conjunction with the first aspect, according to one embodiment of this application, the marine phase includes a first anti-slip body and a second anti-slip body; in a first contact environment, the dynamic friction coefficient of the first anti-slip body is greater than the dynamic friction coefficient of the second anti-slip body and the polymer matrix; in a second contact environment, the dynamic friction coefficient of the second anti-slip body is greater than the dynamic friction coefficient of the first anti-slip body and the polymer matrix, wherein the first contact environment is a dry environment on the contact surface without the application of a liquid medium, and the second contact environment is a wet environment on the contact surface with the application of a liquid medium.

[0012] The first and second anti-slip bodies are suitable for different contact environments. The first anti-slip body has a relatively large coefficient of dynamic friction in a dry environment where no liquid medium is applied to the contact surface, thus providing friction in a dry environment. The second anti-slip body has a relatively large coefficient of dynamic friction in a wet environment where a liquid medium is applied to the contact surface, thus providing friction in a wet environment. The first and second anti-slip bodies are jointly disposed in the marine environment, allowing the marine environment to generate corresponding frictional effects according to changes in the contact environment, thereby reducing the possibility that the anti-slip performance of using only one anti-slip body will be limited by dry or wet environments.

[0013] In conjunction with the first aspect, according to one embodiment of this application, the first anti-slip body contains a siloxy functional group; and / or, the molecular chain ends of the second anti-slip body contain polar functional groups; and / or, the marine phase further includes a matrix polymer, the matrix polymer including functional groups, the functional groups being used to improve the compatibility between the matrix polymer and the first and second anti-slip bodies, so that the first anti-slip body, the second anti-slip body, and the matrix polymer together constitute the marine phase.

[0014] The siloxy functional groups in the first anti-slip agent and the polar functional groups at the ends of the molecular chains of the second anti-slip agent can modulate the interfacial properties of the first and second anti-slip agents. When the marine phase also includes a matrix polymer, the functional groups in the matrix polymer can improve the compatibility between the matrix polymer and the first and second anti-slip agents, reduce the possibility of macroscopic phase separation during blending, and facilitate the co-formation of the marine phase by all three.

[0015] In conjunction with the first aspect, according to one embodiment of this application, the first anti-slip body comprises a siloxy-functionalized styrene-ethylene / butene-styrene block copolymer; and / or, the second anti-slip body comprises a bi-terminated functionalized solution-polymerized styrene-butadiene rubber; and / or, the matrix polymer comprises an ethylene-vinyl acetate copolymer.

[0016] In conjunction with the first aspect, according to one embodiment of this application, the island phase, by weight, comprises: 4 to 6 parts of spherical nano-silica, 6 to 10 parts of silicone microspheres, and 8 to 15 parts of hydroxyl-terminated polydimethylsiloxane; and / or, by weight, the marine phase comprises: 20 to 40 parts of siloxy-functionalized styrene-ethylene / butene-styrene block copolymer, 10 to 30 parts of bi-terminated functionalized solution-polymerized styrene-butadiene rubber, and 15 to 40 parts of ethylene-vinyl acetate copolymer.

[0017] In conjunction with the first aspect, according to one embodiment of this application, a plurality of pores are formed in the polymer matrix; and / or, the polymer matrix includes one or more of ethylene-vinyl acetate copolymer, random polyolefin elastomer, olefin block copolymer and ethylene-butyl acrylate copolymer.

[0018] To achieve the above objectives, in a second aspect, this application provides a method for preparing a wear-resistant and anti-slip material, comprising: preparing functional units, the functional units including a marine phase and an island phase dispersed in the marine phase; mixing the functional units with a polymer matrix to disperse multiple functional units in a polymer matrix formed by the polymer matrix, thereby obtaining a wear-resistant and anti-slip material; wherein, under the same test conditions, the wear volume of the island phase is smaller than that of the marine phase and the polymer matrix, and the dynamic friction coefficient of the marine phase is greater than that of the island phase and the polymer matrix.

[0019] By pre-preparing functional units comprising marine and island phases, and then mixing these functional units with the polymer matrix, disordered dispersion that would occur when the components constituting the marine and island phases are added directly to the polymer matrix can be avoided. The island phase is pre-dispersed in the marine phase, allowing the marine phase to provide support and buffering during subsequent mixing. Multiple functional units are dispersed within the polymer matrix formed by the polymer matrix, enabling the island phases to indirectly bond with the polymer matrix through the marine phase. This reduces the likelihood of the island phase separating or detaching from the polymer matrix during mixing and use, and allows the resulting wear-resistant and anti-slip material to acquire wear-resistant and anti-slip properties through the island and marine phases respectively.

[0020] In conjunction with the second aspect, according to one embodiment of this application, the preparation of the functional unit includes: pre-processing a first wear-resistant particle, a second wear-resistant particle, and an island phase matrix, such that the first wear-resistant particle and the second wear-resistant particle are distributed in the island phase matrix and are bonded to each other through the island phase matrix to obtain an island phase premix; sequentially melt-blending and granulating the island phase premix with a first anti-slip body, a second anti-slip body, and a matrix polymer, such that the first anti-slip body, the second anti-slip body, and the matrix polymer form a marine phase, and the island phase formed by the island phase premix is ​​dispersed in the marine phase to obtain the functional unit.

[0021] First, the first and second wear-resistant particles and the island phase matrix are pre-processed, allowing the first and second wear-resistant particles to be pre-distributed within the island phase matrix and bonded together by the matrix to form an island phase premix. The island phase premix is ​​then melt-blended and granulated with the first and second anti-slip agents and the matrix polymer, causing the first and second wear-resistant particles to form island phases within the island phase matrix and dispersed within the marine phase formed by the first and second anti-slip agents and the matrix polymer. This staged processing method enhances the bonding between the first and second wear-resistant particles and the island phase matrix, and further supports and surrounds the island phases through the marine phase, thereby reducing the possibility of loosening or detachment of the first and second wear-resistant particles during melt blending and subsequent use.

[0022] In conjunction with the second aspect, according to one embodiment of this application, the functional unit is mixed with the polymer base material, including: pre-mixing the functional unit with the polymer base material, adding a crosslinking agent and a foaming agent after mixing, and then performing crosslinking and foaming to form multiple pores in the polymer matrix.

[0023] The beneficial effects of the second aspect described above can be referred to in the first aspect or any possible implementation of the first aspect, and will not be elaborated here. Based on the implementations provided in the above aspects, this application can also be further combined to provide more implementations.

[0024] Other advantages, objectives and features of this application will be partly apparent from the description below, and partly understood by those skilled in the art through study and practice of this application. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments or related technologies of this application, the accompanying drawings used in the description of the embodiments or related technologies will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0026] Figure 1 This is one of the flowcharts illustrating the preparation method of the wear-resistant and anti-slip material provided in the embodiments of this application; Figure 2 This is a second schematic flowchart of the preparation method of the wear-resistant and anti-slip material provided in the embodiments of this application; Figure 3 This is a composition table of functional units 1-14 prepared in this application; Figure 4 This is a component table of some embodiments prepared in this application; Figure 5This is a component table of another set of embodiments and comparative examples prepared in this application; Figure 6 This is a table of test results for some of the embodiments prepared in this application; Figure 7 This is a table of test results for another set of embodiments and comparative examples prepared in this application. Detailed Implementation

[0027] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0028] Ethylene-vinyl acetate copolymer (EVA) foam materials are lightweight, soft, elastic, and have good cushioning properties, making them widely used in products such as sports shoe soles. After foaming, ethylene-vinyl acetate copolymers, random polyolefin elastomers (POE), olefin block copolymers (OBC), ethylene propylene diene monomer (EPDM) rubber, and styrene-based thermoplastic elastomers can achieve lower density and better cushioning performance. However, the porous structure formed by foaming can also reduce the material's wear resistance and anti-slip properties, especially when there is a liquid medium such as water on the contact surface, where the friction between the foam material and the contact surface is easily affected by the liquid film.

[0029] To improve the abrasion resistance of foamed materials, macromolecular silicone, silicone oil, modified silicone abrasion-resistant masterbatch, inorganic fillers, or fiber reinforcements can be added to the polymer matrix. Some silicon-based abrasion-resistant components may migrate to the material surface and form a lubricating surface layer, which can reduce wear but may also lower the coefficient of friction. Inorganic fillers or fiber reinforcements can improve the hardness and load-bearing capacity of the material, but the interfacial bonding between the functional particles and the polymer matrix may be insufficient due to differences in polarity, surface energy, hardness, or deformation capacity, thus affecting the material's flexibility, foaming properties, compression properties, or wearing comfort. Bonding an unfoamed rubber outsole under a foamed midsole can also achieve certain abrasion resistance and anti-slip properties, but unfoamed rubber outsoles usually have a higher density, which may increase the weight of the sole. When functional particles are directly incorporated into the polymer matrix, the interface between the functional particles and the polymer matrix may also experience significant local stress during repeated friction, compression, or bending, leading to loosening or detachment of the functional particles. While increasing the amount of functional particles may enhance wear resistance, it may also affect the material's anti-slip properties, foaming properties, and mechanical properties.

[0030] To solve the above-mentioned technical problems, in a first aspect, this application provides a wear-resistant and anti-slip material, including a polymer matrix and a plurality of functional units dispersed in the polymer matrix; the functional units have an island structure and include a marine phase and an island phase dispersed in the marine phase; the wear volume of the island phase is smaller than the wear volume of the marine phase and the polymer matrix, and the dynamic friction coefficient of the marine phase is greater than the dynamic friction coefficient of the island phase and the polymer matrix.

[0031] This application disperses functional units within a polymer matrix, each containing both marine and island phases. The wear volume of the island phase is smaller than that of the marine phase and the polymer matrix, thus enabling the island phase to withstand wear loads generated during material use and reducing direct wear on the functional units and the polymer matrix. The marine phase has a higher coefficient of dynamic friction than the island phase and the polymer matrix, increasing friction between the functional units and the contact surfaces. Therefore, the functional units, through the island and marine phases respectively, provide wear resistance and anti-slip properties, allowing the functional units dispersed within the polymer matrix to simultaneously possess both wear-resistant and anti-slip properties.

[0032] Meanwhile, since the island phase is dispersed within the marine phase, the marine phase can, to some extent, serve as a buffer zone and interfacial transition zone between the island phase and the polymer matrix. When the material is subjected to friction, compression, or bending, the marine phase can buffer the stress caused by the performance differences between the island phase and the polymer matrix through its own deformation, reducing the direct stress concentration at the interface between the island phase and the polymer matrix. Compared to directly incorporating wear-resistant components into the polymer matrix, this island structure reduces the possibility of the island phase loosening or detaching from the polymer matrix during repeated wear, thus maintaining the wear-resistant properties of the island phase and the anti-slip properties of the marine phase, thereby achieving a balance between the material's wear resistance and anti-slip performance.

[0033] It should be noted that functional units can be composite particles, composite granules, or composite micro-regions pre-formed and dispersed in the polymer matrix by marine and island phases. A functional unit exhibiting an island structure means that within the functional unit, the marine phase forms a phase region supporting the island phase, which is distributed as a dispersed phase within the marine phase. The island structure does not require that each functional unit or each island phase have identical geometry, size, and phase ratio. Furthermore, during subsequent mixing, the marine phase of the functional unit and the polymer matrix can undergo mutual diffusion, mutual penetration, or partial compatibility at the interface, forming an interfacial transition region between the functional unit and the polymer matrix. A clear geometric boundary between the functional unit and the polymer matrix is ​​not a necessary condition for a functional unit; as long as the functional region dispersed in the polymer matrix can still be identified based on the marine phase region surrounding the island phase, the spatial distribution of each component, or phase differences, it can be considered a functional unit.

[0034] The island phase can be spherical, near-spherical, ellipsoidal, irregularly granular, or a composite region formed by multiple particles and the island phase matrix. The marine phase can continuously surround the island phase or be distributed substantially continuously among multiple island phases. As long as the island phase is dispersed in the marine phase and the marine phase can form a supporting region, buffer region, or interface transition region between the island phase and the polymer matrix, it can be regarded as the island structure referred to in this application.

[0035] In some embodiments, the functional unit is a pre-prepared island-structured wear-resistant and anti-slip agent. The island phase is composed of nano-silicone spheres, silicone microspheres, and hydroxyl-terminated polydimethylsiloxane forming a wear-resistant structure; the sea phase is composed of siloxy-functionalized styrene-ethylene / butene-styrene block copolymer, bi-terminated solution-polymerized styrene-butadiene rubber, and ethylene-vinyl acetate copolymer forming an anti-slip elastic phase. By pre-forming the wear-resistant island phase and the anti-slip sea phase functional distribution, and then adding the functional unit to the polymer matrix, the wear-resistant component and the anti-slip component can be co-dispersed in the polymer matrix in a predetermined spatial relationship.

[0036] When a material is subjected to wear loads, the island phase can preferentially bear at least part of the wear load and act as a local wear-resistant support structure to reduce material loss from the marine phase and the polymer matrix. As the material surface gradually wears down, functional units at different depths can be exposed to the contact surface in sequence, and the wear-resistant particles in the island phase can continuously participate in the wear resistance. The marine phase can be exposed to the contact surface and provide friction, while utilizing its own flexibility and elasticity to maintain the deformation capacity of the material surface.

[0037] Without being constrained by specific theories, the silicon-containing components in the island phase may gradually be exposed or migrate to the surface during friction and material surface renewal, thus participating in the formation of a wear-resistant surface. The marine phase can support and surround the island phase, and form a buffer and transition between the island phase and the polymer matrix, thereby reducing the possibility of rigid wear-resistant components loosening or falling off directly from the polymer matrix interface.

[0038] It should be noted that the first and second wear-resistant particles in the functional unit are pre-bonded by an island phase matrix or at least partially coated by an island phase matrix, and then supported and surrounded by a marine phase. This structure differs from the disordered agglomerates formed during processing due to poor dispersion. The composition, size hierarchy, and phase relationship of the former can be controlled through pre-processing and melt blending processes, while disordered agglomerates usually lack stable internal bonding and a marine phase transition structure.

[0039] When the total doping amount of functional components is the same or similar, compared to directly dispersing wear-resistant particles and anti-slip components into the polymer matrix, pre-formed functional units can keep the wear-resistant particles within a localized area bound by an island phase matrix and supported by a marine phase. The marine phase can reduce localized stress concentration caused by rigid wear-resistant particles being directly exposed at the polymer matrix interface and provide anti-slip properties when the functional units are exposed on the material surface. Therefore, a unit amount of functional component can more fully participate in wear resistance and anti-slip effects.

[0040] The aforementioned island structure is used to reduce the possibility of loosening and detachment of island phases or wear-resistant particles, but it does not mean that particle detachment can be completely avoided under all usage conditions. The specific effect can vary depending on the size of the functional unit, the island phase content, the marine phase content, the compatibility of the marine phase with the polymer matrix, the degree of crosslinking, the foaming ratio, and the usage environment.

[0041] In this application, wear volume can represent the volume of material lost by a sample under specified wear test conditions. The smaller the wear volume, the better the wear resistance of the corresponding material under the same test conditions. The wear volumes of island phase, marine phase, and polymer matrix can be obtained by preparing test samples using the corresponding components and conducting tests under the same sample size, wear load, wear path, contact material, test speed, and test environment.

[0042] The coefficient of kinetic friction represents the ratio of frictional force to normal force when a sample moves relative to a specified contact surface. The coefficients of kinetic friction for marine, island, and polymer matrices can be obtained by preparing test samples using the corresponding components and testing them under the same contact surface, normal load, relative speed, test temperature, and contact environment.

[0043] In conjunction with the first aspect, according to one embodiment of this application, the island phase includes an island phase matrix and a first wear-resistant particle group and a second wear-resistant particle group distributed in the island phase matrix. The first wear-resistant particle group includes a plurality of first wear-resistant particles, and the second wear-resistant particle group includes a plurality of second wear-resistant particles. The first wear-resistant particles and the second wear-resistant particles belong to different size levels, and the wear volume of both the first wear-resistant particles and the second wear-resistant particles is smaller than the wear volume of the island phase and the polymer matrix.

[0044] The first and second wear-resistant particle groups each comprise multiple wear-resistant particles belonging to different size levels, creating a multi-sized wear-resistant structure within the island phase. Wear-resistant particles of different size levels can withstand wear at different spatial scales. Larger wear-resistant particles form a wear-resistant support framework, while smaller particles are distributed among the larger particles, thus increasing the number of particles in the island phase capable of bearing wear loads. Both the first and second wear-resistant particles have a smaller wear volume than the marine phase and the polymer matrix, allowing them to jointly bear the wear load applied to the island phase and reduce material loss due to continuous friction.

[0045] It should be noted that the first wear-resistant particles and the second wear-resistant particles belong to different size levels. This means that the first wear-resistant particle group and the second wear-resistant particle group have identifiable size differences in average particle size or main particle size distribution range. It does not mean that any larger and smaller particles in the same particle group due to production precision are named as the first wear-resistant particles and the second wear-resistant particles respectively.

[0046] In some embodiments, the first wear-resistant particle group and the second wear-resistant particle group are made from particulate raw materials of different specifications or different size ranges. The first wear-resistant particles and the second wear-resistant particles may correspond to the nanoscale level and the microscale level, respectively, or they may adopt other size levels that can be distinguished from each other.

[0047] Larger second wear-resistant particles can form micron-scale support structures within the island phase, while smaller first wear-resistant particles can be distributed between the second wear-resistant particles or at the interface between the second wear-resistant particles and the island phase matrix. The first and second wear-resistant particles together constitute a multi-sized wear-resistant structure, which is beneficial for dispersing wear loads of different sizes and reducing the possibility of large voids forming between particles of a single size.

[0048] In conjunction with the first aspect, according to one embodiment of this application, the first wear-resistant particle is a nano-sized particle, and the second wear-resistant particle is a micron-sized particle; and / or, the average particle size of the first wear-resistant particle is 10 to 100 nm; and / or, the average particle size of the second wear-resistant particle is 5 to 10 μm.

[0049] For example, the average particle size of the first wear-resistant particle can be 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, or 100nm, or other values ​​within the range of 10 to 100nm. For example, the average particle size of the second wear-resistant particle can be 5μm, 6μm, 7μm, 8μm, 9μm, or 10μm, or other values ​​within the range of 5 to 10μm.

[0050] In some embodiments, the first wear-resistant particle can be a nanoscale particle with a particle size in the range of 5 to 100 nm, preferably a nanoscale particle with an average particle size in the range of 10 to 100 nm, and more preferably a nanoscale particle with a particle size in the range of 50 to 100 nm. The second wear-resistant particle can be a micrometer-sized particle with a particle size in the range of 1 to 100 μm, preferably a micrometer-sized particle with an average particle size in the range of 5 to 10 μm, and more preferably a micrometer-sized particle with a particle size in the range of 8 to 10 μm.

[0051] The first wear-resistant particle uses nanoscale particles, which helps to increase the contact area between the first wear-resistant particle and the island phase matrix, and allows it to fill and distribute within the island phase at a smaller scale. The second wear-resistant particle uses micron-scale particles, which can provide wear-resistant support at the micron scale. The combination of the two can enable the island phase to form a wear-resistant structure with both nanoscale and micron-scale components.

[0052] It should be noted that there is no fixed correspondence between the material types and size levels of silica and silicone particles. In one embodiment, the silica particles are nanoscale particles and the silicone particles are micrometer-scale particles; in another embodiment, the silica particles are micrometer-scale particles and the silicone particles are nanoscale particles. As long as the silica and silicone particles belong to mutually distinguishable size levels and can form island phases together with hydroxyl-terminated polydimethylsiloxane, wear loads can be borne by particles of different size levels at different spatial scales.

[0053] Specifically, in embodiments where the silica particles are nanoscale particles and the silicone particles are micrometer-scale particles, the average particle size of the silica particles can be 10–100 nm, and the average particle size of the silicone particles can be 5–10 μm.

[0054] In conjunction with the first aspect, according to one embodiment of this application, the first wear-resistant particle comprises nano-silica; and / or, the second wear-resistant particle comprises silicone microspheres; and / or, the island phase matrix is ​​hydroxyl-terminated polydimethylsiloxane; and / or, at least one of the first wear-resistant particle and the second wear-resistant particle is a spherical particle.

[0055] Nano-silica can be nano-silica spheres with a regular or near-regular spherical structure. Nano-silica possesses high hardness, wear resistance, and specific surface area, enabling it to form nanoscale wear-resistant support regions within island phases. The nanoscale size also increases the contact area between nano-silica and the island phase matrix, thus facilitating a stable bond between the two. In some theoretical explanations, the wear resistance and impact resistance exhibited by nano-silica can be attributed to its nanoscale size, high specific surface area, high surface activity, and size effect at the nanoscale. The above theoretical explanations are used to aid in understanding the role of nano-silica and do not constitute a limitation on the scope of protection of this application.

[0056] Silicone microspheres can be organic-inorganic composite particles mainly composed of organosilicon derivatives and metal complexes, and can possess a three-dimensional cross-linked network molecular structure. Silicone microspheres can be regularly spherical, with a relatively smooth surface and good flowability. The organic functional groups in silicone microspheres facilitate the formation of compatible interfaces with organic materials and polymers.

[0057] When used as reinforcing particles, silicone microspheres can improve the hardness, compressive strength, and wear resistance of the island phase. During plastic processing, silicone microspheres can also reduce melt viscosity, improve flowability, and enhance mold release and material surface condition. These effects of silicone microspheres can vary depending on their composition, degree of cross-linking, particle size, and dosage.

[0058] The hydroxyl-terminated polydimethylsiloxane can be a dihydroxyl-terminated polydimethylsiloxane, and its viscosity can be 1000–3000 cps. For example, the viscosity of the hydroxyl-terminated polydimethylsiloxane can be 1000 cps, 1200 cps, 1500 cps, 1800 cps, 2000 cps, 2500 cps, or 3000 cps.

[0059] The hydroxyl groups at the ends of the polydimethylsiloxane molecular chains can interact with the hydroxyl groups on the surface of nano-silica. Under appropriate processing conditions, the terminal hydroxyl groups of the polydimethylsiloxane and the hydroxyl groups on the surface of nano-silica can undergo condensation and form Si-O-Si bonds, thereby enhancing the interfacial bonding between the two.

[0060] The molecular chains of hydroxyl-terminated polydimethylsiloxane can also physically adsorb and coat at least part of the surface of nano-silica and silicone microspheres, thereby improving the thermal stability, surface compatibility, and dispersibility of the first and second wear-resistant particles. Hydroxyl-terminated polydimethylsiloxane can combine multiple first and second wear-resistant particles into an island-phase premix, and form a wear-resistant composite region as the island-phase matrix.

[0061] At least one of the silica particles and silicone particles can be spherical or near-spherical. Spherical or near-spherical particles experience relatively less directional resistance during mixing, which is beneficial for particle dispersion in the island phase matrix and reduces local stress concentration caused by sharp edges. When at least one of the silica particles and silicone particles is ellipsoidal or irregularly shaped, hydroxyl-terminated polydimethylsiloxane can retain the particle in the island phase through wetting, coating, physical adsorption, or bonding. Spherical particles do not require them to be perfectly spherical in a geometric sense. Particles may be near-spherical or ellipsoidal due to manufacturing errors, surface structure, or processing deformation, and can be considered spherical particles as long as their overall outline does not exhibit obvious needle-like, plate-like, or other highly anisotropic morphologies.

[0062] In other embodiments, at least one of the silica particles and silicone particles may be non-spherical particles. Non-spherical particles may be ellipsoidal or irregularly shaped. For non-spherical particles, their average particle size may be expressed as the equivalent particle size. The equivalent particle size refers to the diameter of a spherical particle with the same projected area or volume as the corresponding particle.

[0063] In one embodiment, the silica particles are nearly spherical or irregular particles with an average particle size of 10–100 nm, and the silicone particles are spherical particles with an average particle size of 5–10 μm. In another embodiment, the silica particles are spherical particles with an average particle size of 10–100 nm, and the silicone particles are nearly spherical or ellipsoidal particles with an average particle size of 5–10 μm. In yet another embodiment, both the silica particles and the silicone particles are irregular granular.

[0064] Regardless of whether the silica particles and silicone particles are spherical, near-spherical, ellipsoidal, or irregularly shaped, hydroxyl-terminated polydimethylsiloxane can distribute and maintain the silica particles and silicone particles in the island phase through wetting, coating, physical adsorption, or interparticle linkage.

[0065] In conjunction with the first aspect, according to one embodiment of this application, the marine phase includes a first anti-slip body and a second anti-slip body; in a first contact environment, the dynamic friction coefficient of the first anti-slip body is greater than the dynamic friction coefficient of the second anti-slip body and the polymer matrix; in a second contact environment, the dynamic friction coefficient of the second anti-slip body is greater than the dynamic friction coefficient of the first anti-slip body and the polymer matrix, wherein the first contact environment is a dry environment on the contact surface without the application of a liquid medium, and the second contact environment is a wet environment on the contact surface with the application of a liquid medium.

[0066] The first and second anti-slip bodies are suitable for different contact environments. The first anti-slip body has a relatively large coefficient of dynamic friction in a dry environment where no liquid medium is applied to the contact surface, thus providing friction in a dry environment. The second anti-slip body has a relatively large coefficient of dynamic friction in a wet environment where a liquid medium is applied to the contact surface, thus providing friction in a wet environment. The first and second anti-slip bodies are jointly disposed in the marine environment, allowing the marine environment to generate corresponding frictional effects according to changes in the contact environment, thereby reducing the possibility that the anti-slip performance of using only one anti-slip body will be limited by dry or wet environments.

[0067] The first contact environment can be an environment in which no liquid medium is actively applied to either the test specimen or the contact surface. The second contact environment can be an environment in which water, an aqueous solution, or other liquid medium is applied between the test specimen and the contact surface. In some test embodiments, water is used as the liquid medium in the second contact environment.

[0068] It should be noted that, except for whether a liquid medium is applied, when comparing the frictional properties of different materials, the sample preparation method, contact surface material, normal load, movement speed, test temperature and other test conditions should be kept the same or equivalent so that the obtained dynamic friction coefficients are comparable.

[0069] The first and second anti-slip bodies can be elastic polymers or composite materials with elastic polymers as the main component. The first and second anti-slip bodies together form the marine phase. It is not required that the two are completely homogeneous at the molecular scale, as long as they can jointly form the phase region that supports and surrounds the island phase, and can exert corresponding frictional effects in the first and second contact environments, respectively.

[0070] In conjunction with the first aspect, according to one embodiment of this application, the first anti-slip body contains a siloxy functional group; and / or, the molecular chain ends of the second anti-slip body contain polar functional groups; and / or, the marine phase further includes a matrix polymer, the matrix polymer including functional groups, the functional groups being used to improve the compatibility between the matrix polymer and the first and second anti-slip bodies, so that the first anti-slip body, the second anti-slip body, and the matrix polymer together constitute the marine phase.

[0071] The siloxy functional groups in the first anti-slip agent and the polar functional groups at the ends of the molecular chains of the second anti-slip agent can modulate the interfacial properties of the first and second anti-slip agents. When the marine phase also includes a matrix polymer, the functional groups in the matrix polymer can improve the compatibility between the matrix polymer and the first and second anti-slip agents, reduce the possibility of macroscopic phase separation during blending, and facilitate the co-formation of the marine phase by all three.

[0072] The siloxy functional group can serve as an interaction site between the primary anti-slip agent and components containing hydroxyl or other polar groups, and can improve the interfacial bonding state through covalent interactions, hydrogen bonding, or other intermolecular interactions. The primary anti-slip agent can also play a compatibilizing role between the marine and island phases, thereby improving the interfacial bonding between the primary wear-resistant particles such as nano-silica and the marine phase, as well as hydroxyl-terminated polydimethylsiloxane.

[0073] The polar functional groups at the ends of the molecular chains of the second anti-slip agent may include terminal amino groups, terminal siloxane groups, or other groups capable of interacting polarly with water molecules. In the second contact environment, the polar functional groups can form hydrogen bonds or other polar interactions with water molecules, thereby changing the wetting state of the material surface.

[0074] Without being constrained by specific theories, the aforementioned polar effect is beneficial for disturbing the continuous water film between the sample and the contact surface, increasing the microscopic contact area between the material and the contact surface, thereby improving the coefficient of friction in a humid environment. The specific degree of this effect can vary with the type and content of polar functional groups, the surface state of the contact surface, and the composition of the liquid medium.

[0075] The functional groups in the matrix polymer can be polar functional groups. When the matrix polymer is an ethylene-vinyl acetate copolymer, the functional groups can be provided by vinyl acetate structural units. Vinyl acetate structural units are beneficial for improving the melt flowability and processability of the matrix polymer, and reducing processing energy consumption and shear heat generation during twin-screw granulation.

[0076] The matrix polymer can also improve the plasticity and extensibility of the blend, reducing the possibility of extrusion flow interruption, melt breakage, or die blockage due to the high rigidity of the first and second wear-resistant particles. The matrix polymer has a relatively stable response to shear forces, which can help to achieve uniform blending of the first anti-slip body, the second anti-slip body, and the island phase premix.

[0077] The vinyl acetate structural unit can also form weak hydrogen bonds, electrostatic interactions, or other intermolecular interactions with the first anti-slip body, the second anti-slip body, and hydroxyl-terminated polydimethylsiloxane, thereby improving interfacial compatibility, reducing disordered aggregation of island phases, and promoting the formation of marine phases by the first anti-slip body, the second anti-slip body, and the matrix polymer.

[0078] In conjunction with the first aspect, according to one embodiment of this application, the first anti-slip body comprises a siloxy-functionalized styrene-ethylene / butene-styrene block copolymer (hereinafter also referred to as siloxy-functionalized SEBS); and / or, the second anti-slip body comprises a bi-terminated functionalized solution-polymerized styrene-butadiene rubber; and / or, the matrix polymer comprises an ethylene-vinyl acetate copolymer.

[0079] Siloxy-functionalized styrene-ethylene / butene-styrene block copolymers can be obtained by introducing siloxy-functionalized monomers into the polymerization ends or main chain of the styrene-ethylene / butene-styrene block copolymer. Siloxy-functionalized monomers can form reactive siloxy functional groups in the styrene-ethylene / butene-styrene block copolymer.

[0080] The siloxy grafting rate of the siloxy-functionalized styrene-ethylene / butene-styrene block copolymer can be 2% to 10%, and the styrene content can be 20% to 40%. For example, the siloxy grafting rate can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%; and the styrene content can be 20%, 25%, 30%, 33%, 35%, or 40%. It should be noted that unless otherwise specified in the raw material specifications or test methods, the siloxy grafting rate and styrene content are calculated based on the total mass of the corresponding polymer.

[0081] In a preferred embodiment, the siloxy group grafting rate is 5% to 6%, and the styrene content is 30% to 35%. Exemplarily, the siloxy group grafting rate can be 5%, 5.5%, or 6%, and the styrene content can be 30%, 31%, 32%, 33%, 34%, or 35%.

[0082] The saturated soft segment structure of styrene-ethylene / butene-styrene block copolymers provides elasticity and surface deformation capability. The introduction of siloxy functional groups can provide interfacial interaction sites, improve the bonding state between the first anti-slip agent and the polar component and island phase, and help to regulate the frictional properties between the material surface and the contact surface.

[0083] In the first contact environment, the siloxy-functionalized styrene-ethylene / butene-styrene block copolymer can increase the actual contact between the material and the contact surface by utilizing its elasticity and surface deformation capabilities, and provide dry anti-slip effect by regulating surface properties through siloxy functional groups.

[0084] Dual-terminal functionalized solution-polymerized styrene-butadiene rubber (SBR) can be achieved by incorporating polar functional groups at both ends of the SBR molecular chain. This dual-terminal functionalization design creates interfacial interaction sites at both ends of the molecular chain and enhances the bonding between the dual-terminal functionalized SBR and nano-silica, hydroxyl-terminated polydimethylsiloxane, and other polar components.

[0085] The English name for solution-polymerized styrene-butadiene rubber is solution-polymerized styrene-butadiene rubber, abbreviated as SSBR. This example uses bi-terminal functionalized solution-polymerized styrene-butadiene rubber. The styrene content of the bi-terminal functionalized solution-polymerized styrene-butadiene rubber can be 34%–35%, the vinyl content can be 38%–40%, and the Mooney viscosity can be 40–60. The Mooney viscosity is determined according to GB / T1232.1-2016, and the test conditions are ML(1+4) 100°C.

[0086] For example, the styrene content can be 34%, 34.1%, 34.5%, or 35%; the vinyl content can be 38%, 38.7%, 39%, 39.5%, or 40%; and the Mooney viscosity can be 40, 45, 50, 55, or 60.

[0087] The polar functional groups at the ends of the solution-polymerized styrene-butadiene rubber (SBR) molecular chains can include terminal amino groups or terminal siloxane groups. In a water-containing secondary contact environment, these polar functional groups can adsorb water molecules through hydrogen bonding or other polar interactions, forming a dynamic hydrophilic interface on the material surface. This interface helps to disrupt or disturb the water film between the sole and the contact surface, increasing the microscopic contact area and thus improving the coefficient of friction in a wet environment.

[0088] The matrix polymer can be an ethylene-vinyl acetate copolymer with a vinyl acetate (VA) content of 20% to 30%. For example, the vinyl acetate content can be 20%, 22%, 24%, 26%, 28%, or 30%.

[0089] Ethylene-vinyl acetate copolymers used in marine phases can exhibit relatively high melt flow rates, thereby improving the melt blending effect of the first anti-slip agent, the second anti-slip agent, and the island phase premix. The ethylene segments in the ethylene-vinyl acetate copolymer provide elasticity and compatibility with non-polar polymer components, while the vinyl acetate structural units provide polar functional groups and good processing flowability.

[0090] In conjunction with the first aspect, according to one embodiment of this application, the island phase, by weight, comprises: 4-6 parts of spherical nano-silica, 6-10 parts of silicone microspheres, and 8-15 parts of hydroxyl-terminated polydimethylsiloxane; and / or, by weight, the marine phase comprises: 20-40 parts of siloxy-functionalized styrene-ethylene / butene-styrene block copolymer, 10-30 parts of bi-terminated functionalized solution-polymerized styrene-butadiene rubber, and 15-40 parts of ethylene-vinyl acetate copolymer. Exemplarily, the spherical nano-silica may be 4 parts, 4.5 parts, 5 parts, 5.5 parts, or 6 parts; the silicone microspheres may be 6 parts, 7 parts, 8 parts, 9 parts, or 10 parts; and the hydroxyl-terminated polydimethylsiloxane may be 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, or 15 parts. For example, the siloxy-functionalized styrene-ethylene / butene-styrene block copolymer can be 20 parts, 25 parts, 30 parts, 35 parts or 40 parts; the bi-terminal functionalized solution-polymerized styrene-butadiene rubber can be 10 parts, 15 parts, 20 parts, 25 parts or 30 parts; and the ethylene-vinyl acetate copolymer can be 15 parts, 20 parts, 25 parts, 30 parts, 35 parts or 40 parts.

[0091] In some specific embodiments, based on the weight parts of each raw material of the functional unit, the functional unit may include 4 to 6 parts of spherical nano-silica, 6 to 10 parts of silicone microspheres, 8 to 15 parts of hydroxyl-terminated polydimethylsiloxane, 20 to 40 parts of siloxy-functionalized styrene-ethylene / butene-styrene block copolymer, 10 to 30 parts of bi-terminated functionalized solution-polymerized styrene-butadiene rubber, and 15 to 40 parts of ethylene-vinyl acetate copolymer.

[0092] In some extended embodiments, the amount of spherical nano-silica can be 3 to 6 parts, the amount of silicone microspheres can be 5 to 10 parts, the amount of hydroxyl-terminated polydimethylsiloxane can be 8 to 15 parts, the amount of siloxy-functionalized styrene-ethylene / butene-styrene block copolymer can be 20 to 40 parts, the amount of bi-terminated functionalized solution-polymerized styrene-butadiene rubber can be 10 to 30 parts, and the amount of ethylene-vinyl acetate copolymer can be 15 to 50 parts.

[0093] The preferred composition is 4-6 parts spherical nano-silica, 6-10 parts silicone microspheres, 8-15 parts hydroxyl-terminated polydimethylsiloxane, 20-40 parts siloxy-functionalized styrene-ethylene / butene-styrene block copolymer, 10-30 parts bi-terminated functionalized solution-polymerized styrene-butadiene rubber, and 15-40 parts ethylene-vinyl acetate copolymer, so that the island phase can provide wear resistance, while the marine phase can provide corresponding anti-slip properties in both dry and wet environments.

[0094] Increasing the relative amounts of spherical nano-silica, silicone microspheres, and hydroxyl-terminated polydimethylsiloxane increases the proportion of wear-resistant components in the functional unit, which is beneficial for reducing wear volume, but may reduce the relative proportion of anti-slip components in the marine phase. Increasing the relative amounts of siloxy-functionalized styrene-ethylene / butene-styrene block copolymer and bi-terminated solution-polymerized styrene-butadiene rubber improves both dry and wet anti-slip properties, but may alter the wear volume of the functional unit. Therefore, the amounts of each component can be adjusted according to the target wear resistance and anti-slip performance.

[0095] In conjunction with the first aspect, according to one embodiment of this application, a plurality of pores are formed in the polymer matrix; and / or, the polymer matrix includes one or more of ethylene-vinyl acetate copolymer, random polyolefin elastomer, olefin block copolymer and ethylene-butyl acrylate copolymer (EBA).

[0096] Multiple pores are formed within the polymer matrix, which can reduce the density of the wear-resistant and anti-slip material and give it cushioning and resilience properties.

[0097] Pores can be closed-cell, open-cell, or a combination of both. When used in shoe sole materials, closed-cell pores are preferred to balance lightweight, compressibility, and water absorption control. The shape, size, number, and distribution of pores can be adjusted according to the type and amount of foaming agent, degree of crosslinking, foaming temperature, and molding process. Functional units are dispersed in a polymer matrix with multiple pores and can be distributed on the pore walls or within continuous polymer regions.

[0098] Ethylene-vinyl acetate copolymers possess excellent foaming properties and can be used as one of the main polymers for forming porous structures. In ethylene-vinyl acetate copolymers used as polymer matrices, the vinyl acetate content can be 20%–30%. Some mechanical properties of ethylene-vinyl acetate copolymers used alone can be adjusted by adding random polyolefin elastomers and olefin block copolymers.

[0099] Random polyolefin elastomers can be ethylene-octene copolymers. The molecular chains of ethylene-octene copolymers are relatively flexible, which can improve the resilience, flexibility, and impact resistance of the polymer matrix. The hardness of ethylene-octene copolymers can be 60A to 70A; for example, its hardness can be 60A, 62A, 65A, 68A, or 70A.

[0100] Olefin block copolymers possess high resilience, melting point, and melt strength, and are beneficial for improving the shrinkage and compression resistance of the polymer matrix. The hardness of olefin block copolymers can range from 60A to 75A; for example, the hardness can be 60A, 65A, 70A, or 75A.

[0101] Ethylene-butyl acrylate copolymers possess both polar and nonpolar structures, and exhibit relatively high melting points, melt strength, and low-temperature flexibility, which can improve the compatibility between different polymers and the adhesive strength of foamed materials. The acrylate content in the ethylene-butyl acrylate copolymer can range from 15% to 25%. For example, the acrylate content can be 15%, 17%, 20%, 22%, or 25%.

[0102] In some foaming embodiments, the raw materials forming the polymer matrix may include, by weight, 30-50 parts of ethylene-vinyl acetate copolymer, 10-30 parts of random polyolefin elastomer, 10-20 parts of olefin block copolymer, and 10-20 parts of ethylene-butyl acrylate copolymer. Exemplarily, the ethylene-vinyl acetate copolymer may be 30, 35, 40, 45, or 50 parts; the random polyolefin elastomer may be 10, 15, 20, 25, or 30 parts; the olefin block copolymer may be 10, 12, 15, 18, or 20 parts; and the ethylene-butyl acrylate copolymer may be 10, 12, 15, 18, or 20 parts.

[0103] In some embodiments, the amount of functional unit added can be 5 to 15 parts, the amount of peroxide crosslinking agent added can be 0.5 to 0.7 parts, the amount of foaming agent added can be 3 to 4 parts, the amount of zinc oxide added can be 0.8 to 1.2 parts, and the amount of stearic acid added can be 0.8 to 1.2 parts.

[0104] For example, the functional unit can be 5 parts, 8 parts, 10 parts, 12 parts or 15 parts; the peroxide crosslinking agent can be 0.5 parts, 0.6 parts or 0.7 parts; the foaming agent can be 3 parts, 3.5 parts or 4 parts; the zinc oxide can be 0.8 parts, 1 part or 1.2 parts; and the stearic acid can be 0.8 parts, 1 part or 1.2 parts.

[0105] When the amount of functional units added is too low, the number of functional units distributed in the polymer matrix may be insufficient, which may limit the wear resistance and anti-slip properties. When the amount of functional units added is too high, the wear-resistant component may occupy a large contact area and may affect the foaming properties, compression properties, or anti-slip properties of the polymer matrix. Therefore, the amount of functional units added can be set to 5 to 15 parts depending on the type of polymer matrix and the target properties.

[0106] To solve the above-mentioned technical problems, in the second aspect, please refer to... Figure 1 This application provides a method for preparing a wear-resistant and anti-slip material, comprising: S101. Prepare functional units, including marine facies and island facies dispersed in marine facies; S103. The functional units are mixed with the polymer matrix to disperse multiple functional units in the polymer matrix formed by the polymer matrix, thereby obtaining a wear-resistant and anti-slip material; wherein, under the same test conditions, the wear volume of the island phase is smaller than that of the marine phase and the polymer matrix, and the dynamic friction coefficient of the marine phase is greater than that of the island phase and the polymer matrix.

[0107] By pre-preparing functional units comprising marine and island phases, and then mixing these functional units with the polymer matrix, disordered dispersion that would occur when the components constituting the marine and island phases are added directly to the polymer matrix can be avoided. The island phase is pre-dispersed in the marine phase, allowing the marine phase to provide support and buffering during subsequent mixing. Multiple functional units are dispersed within the polymer matrix formed by the polymer matrix, enabling the island phases to indirectly bond with the polymer matrix through the marine phase. This reduces the likelihood of the island phase separating or detaching from the polymer matrix during mixing and use, and allows the resulting wear-resistant and anti-slip material to acquire wear-resistant and anti-slip properties through the island and marine phases respectively.

[0108] The functional units can be prepared and granulated individually before being added to the polymer base. Pre-granulation gives each functional unit a relatively stable island structure and facilitates the metering, storage, transportation, and mixing of the functional units with the polymer base. The polymer base may include one or more of ethylene-vinyl acetate copolymers, random polyolefin elastomers, olefin block copolymers, and ethylene-butyl acrylate copolymers.

[0109] Comparing the wear volume and dynamic friction coefficient of island phase, marine phase and polymer matrix under the same test conditions means that when comparing the same performance parameters, except for the composition of the tested material, the sample shape, sample size, contact surface, load, movement speed, temperature and environmental conditions are kept the same or equivalent.

[0110] In conjunction with the second aspect, please refer to Figure 2 According to one embodiment of this application, the preparation of the functional unit includes: S201. The first wear-resistant particles, the second wear-resistant particles and the island phase matrix are pre-processed so that the first wear-resistant particles and the second wear-resistant particles are distributed in the island phase matrix and are combined with each other through the island phase matrix to obtain an island phase premix. S203. The island phase premix is ​​melt-blended and granulated with the first anti-slip body, the second anti-slip body and the matrix polymer in sequence, so that the first anti-slip body, the second anti-slip body and the matrix polymer form a marine phase, and the island phase formed by the island phase premix is ​​dispersed in the marine phase to obtain the functional unit.

[0111] First, the first and second wear-resistant particles and the island phase matrix are pre-processed, allowing the first and second wear-resistant particles to be pre-distributed within the island phase matrix and bonded together to form an island phase premix. The island phase premix is ​​then melt-blended and granulated with the first and second anti-slip agents and the matrix polymer, causing the first and second wear-resistant particles to form island phases within the island phase matrix and dispersed within the marine phase formed by the first and second anti-slip agents and the matrix polymer. This staged processing method enhances the bonding between the first and second wear-resistant particles and the island phase matrix, and further supports and surrounds the island phases through the marine phase, thereby reducing the possibility of loosening or detachment of the first and second wear-resistant particles during melt blending and subsequent use.

[0112] Pre-processing may include high-speed mixing, kneading, internal mixing, surface coating, or other processing methods that enable the first wear-resistant particles, the second wear-resistant particles, and the island phase matrix to come into contact with and bond together. Melt blending and granulation can be performed using a twin-screw extruder, a single-screw extruder, or other melt blending equipment, with a twin-screw extruder being preferred.

[0113] In one specific embodiment, 4-6 parts of spherical nano-silica, 6-10 parts of silicone microspheres and 8-15 parts of hydroxyl-terminated polydimethylsiloxane were weighed and put into a high-speed mixer and mixed for 20-30 minutes at a stirring speed of 800-1500 rpm and a mixing temperature of 40-50°C to obtain an island phase premix.

[0114] For example, the pre-processing time can be 20 min, 22 min, 25 min, 28 min or 30 min; the stirring speed can be 800 rpm, 1000 rpm, 1200 rpm or 1500 rpm; and the mixing temperature can be 40℃, 42℃, 45℃, 48℃ or 50℃.

[0115] During the pre-processing, hydroxyl-terminated polydimethylsiloxane is distributed on the surface and in the interparticle spaces of spherical nano-silica and silicone microspheres, so that the spherical nano-silica and silicone microspheres are distributed in the hydroxyl-terminated polydimethylsiloxane and are bonded to each other by the hydroxyl-terminated polydimethylsiloxane.

[0116] Subsequently, 20–40 parts of siloxy-functionalized styrene-ethylene / butene-styrene block copolymer, 10–30 parts of bi-terminated functionalized solution-polymerized styrene-butadiene rubber, and 15–40 parts of ethylene-vinyl acetate copolymer were added to the island phase premix. The mixture was stirred for 10–20 min at a stirring speed of 1000–1500 rpm and at a mixing temperature of 60–80 °C to obtain the blend.

[0117] For example, the mixing time can be 10 min, 12 min, 15 min, 18 min or 20 min; the stirring speed can be 1000 rpm, 1200 rpm, 1300 rpm or 1500 rpm; and the mixing temperature can be 60℃, 65℃, 70℃, 75℃ or 80℃.

[0118] The blend is fed into a twin-screw granulator for melt blending, extrusion and granulation. The processing temperature of the twin-screw granulator can be 120±5℃, that is, 115℃, 118℃, 120℃, 122℃ or 125℃, to obtain functional units with an island structure.

[0119] Under the shearing action of a twin-screw extruder, the island phase premix can form spherical, near-spherical, or ellipsoidal island phases, which are dispersed within the marine phase composed of a first anti-slip material, a second anti-slip material, and a matrix polymer. The interfacial tension and melt viscosity differences between the island phase material and the marine phase material can influence the shape, size, and distribution of the island phases. The processing temperature, screw speed, shear strength, and component ratios can be adjusted according to the target island structure.

[0120] In conjunction with the second aspect, according to one embodiment of this application, the functional unit is mixed with the polymer base material, including: pre-mixing the functional unit with the polymer base material, adding a crosslinking agent and a foaming agent after mixing, and then performing crosslinking and foaming to form multiple pores in the polymer matrix.

[0121] The crosslinking agent can be a peroxide crosslinking agent, and may include at least one of dicumyl peroxide and 1,4-di-tert-butylperoxyisopropylbenzene (BIBP). 1,4-di-tert-butylperoxyisopropylbenzene is preferred.

[0122] The foaming agent may include at least one of N,N′-dinitrospentamethylenetetramine, azodicarbonamide, and 4,4′-oxodibenzenesulfonylhydrazine. N,N′-dinitrospentamethylenetetramine is preferred.

[0123] Premixing the functional units with the polymer base material before adding the crosslinking agent and foaming agent helps reduce the possibility of premature local crosslinking caused by the crosslinking agent or premature decomposition of the foaming agent due to prolonged heating. During the crosslinking and foaming process, the polymer base material forms a crosslinked network, and the foaming agent decomposes to produce gas and form multiple pores in the crosslinked network, thereby obtaining a foamed wear-resistant and anti-slip material.

[0124] In some embodiments, the functional unit is cross-linked and foamed with ethylene-vinyl acetate copolymer, random polyolefin elastomer, olefin block copolymer, and ethylene-butyl acrylate copolymer. The abrasion-resistant and slip-resistant material formed after cross-linking and foaming can be used as athletic shoe soles, especially as foamed midsoles that are in direct contact with the ground.

[0125] The following examples provide some of the raw material selections and grades to illustrate specific embodiments of this application, and do not constitute a limitation on the source or manufacturer of the raw materials. Those skilled in the art can use other raw materials with the same or similar composition, structure, and properties for substitution.

[0126] Ethylene-vinyl acetate copolymer in the polymer matrix: Ethylene-vinyl acetate copolymer has good foaming properties and can be used as the main polymer matrix for preparing foamed materials, which is beneficial for forming a relatively uniform pore structure. In the ethylene-vinyl acetate copolymer used in the polymer matrix, the vinyl acetate content can be 20% to 30%, and the preferred grade is EVA 26061.

[0127] In a specific embodiment, the vinyl acetate molar content of EVA 26061 can be 26%, the hardness can be 80A, the melt mass-flow rate (MI) can be 5.5 g / 10 min, the melting point can be 71 °C, the tensile strength can be 20 MPa, and the elongation at break can be 780%.

[0128] Random polyolefin elastomers: Random polyolefin elastomers can be ethylene-octene copolymers. The molecular chains of ethylene-octene copolymers are relatively flexible and can be used as blending modifiers to improve the resilience, flexibility, and impact resistance of ethylene-vinyl acetate copolymer foam materials.

[0129] The hardness of the random polyolefin elastomer can be 60A to 70A, with POE 8150 being a preferred grade. In a specific embodiment, POE 8150 has a hardness of 70A, a melting point of 55°C, a melt flow rate of 0.5 g / 10 min, a tensile strength of 9.5 MPa, and an elongation at break of 600%.

[0130] Olefin block copolymers: Olefin block copolymers have high resilience and melting point, and can provide relatively high melt strength, which is beneficial to improving the shrinkage resistance and compression properties of foamed materials.

[0131] The hardness of the olefin block copolymer can be 60A to 75A, and the preferred grade is OBC 9107. In a specific embodiment, the hardness of OBC 9107 can be 60A, the melting point can be 121°C, the melt flow rate can be 1.0 g / 10 min, the tensile strength can be 5.1 MPa, and the elongation at break can be 600%.

[0132] Ethylene-butyl acrylate copolymer: Ethylene-butyl acrylate copolymer has a relatively high melting point and melt strength, and possesses both polar and non-polar structures, thus enabling it to form compatible interfaces with a variety of polymers. Ethylene-butyl acrylate copolymer also exhibits good low-temperature flexibility, which is beneficial for improving the adhesive strength of foamed shoe soles.

[0133] The acrylate content in the ethylene-butyl acrylate copolymer can be 15% to 25%, with EBA3717 being a preferred grade. In a specific embodiment, EBA 3717 has an acrylate content of 17%, a hardness of 89A, a melting point of 96°C, a melt flow rate of 7.0 g / 10 min, and a tensile strength of 40 MPa.

[0134] Spherical nano-silica: Spherical nano-silica can be nano-silica spheres (SM) with a particle size of 50–100 nm. Spherical nano-silica can serve as the primary wear-resistant particles and utilize its nanoscale size and high specific surface area to form a nanoscale wear-resistant structure in the island phase.

[0135] Silicone microspheres: Silicone microspheres can have a particle size of 8–10 μm and can be regular or nearly regular spherical. Silicone microspheres can serve as secondary wear-resistant particles and form micron-scale wear-resistant structures within the island phase. Silicone microspheres can possess a three-dimensional cross-linked network structure and organic functional groups to improve their compatibility with organic polymers.

[0136] Hydroxyl-terminated polydimethylsiloxane: Hydroxyl-terminated polydimethylsiloxane can have a viscosity of 1500 cps and can serve as an island phase matrix. Through the interaction between the terminal hydroxyl groups and the hydroxyl groups on the surface of nano-silica, as well as the physical adsorption of the molecular chains, hydroxyl-terminated polydimethylsiloxane can bind or coat spherical nano-silica and silicone microspheres.

[0137] Siloxy-functionalized styrene-ethylene / butene-styrene block copolymer: The hardness of the siloxy-functionalized styrene-ethylene / butene-styrene block copolymer can be 78A, the siloxy grafting rate can be 5%, the styrene content can be 33%, the tensile strength can be 19.8MPa, and the elongation at break can be 1110%.

[0138] This material can be used as a primary anti-slip agent. Its saturated soft segment structure provides elasticity and surface deformation capability, while the siloxy functional groups can serve as interfacial interaction sites and are beneficial for improving friction performance in dry environments.

[0139] Dual-terminated functionalized solution polystyrene-butadiene rubber: The styrene content of dual-terminated functionalized solution polystyrene-butadiene rubber can be approximately 34.1%, the vinyl content can be approximately 38.7%, and the Mooney viscosity can be approximately 40–55. The test conditions are ML 1+4, 100℃. The preferred grade is SSBR3540F.

[0140] This material can be used as a second anti-slip agent. The polar functional groups at both ends of its molecular chain can interact with water molecules in a wet environment, which helps to disturb the water film between the material and the contact surface and increase the micro-contact area.

[0141] Ethylene-vinyl acetate copolymer in marine facies: The vinyl acetate content in the ethylene-vinyl acetate copolymer used in marine facies can be 20% to 30%, and the preferred grade is EVA 28280.

[0142] In a specific embodiment, the vinyl acetate molar content of EVA 28280 can be 28%, the hardness can be 73A, the melt mass flow rate can be 28g / 10min, the melting point can be 67℃, the tensile strength can be 12MPa, and the elongation at break can be 800%.

[0143] EVA 28280 has a relatively high melt flow rate, which is beneficial for its uniform blending with the first anti-slip agent, the second anti-slip agent, and the island phase premix during twin-screw granulation. Its vinyl acetate structural units can improve melt flowability and processing performance, and reduce the risk of shear heat generation and material decomposition.

[0144] EVA 28280 can also improve the plasticity and extensibility of blends, reducing the possibility of extrusion flow interruption or die blockage caused by the high rigidity of spherical nano-silica and silicone microspheres in the island phase. The vinyl acetate structural unit can undergo weak hydrogen bonding, electrostatic interactions, or other intermolecular interactions with siloxy-functionalized styrene-ethylene / butene-styrene block copolymers, bi-terminated solution-polymerized styrene-butadiene rubber, and hydroxyl-terminated polydimethylsiloxane, thereby improving the compatibility within the marine phase and between the marine and island phases.

[0145] Crosslinking agent and blowing agent: The peroxide crosslinking agent may include at least one of dicumyl peroxide and 1,4-di-tert-butylperoxycumyl peroxide, preferably BIBP 14S-FL. BIBP 14S-FL can be white granules with a melting point of 46–52°C. The blowing agent may include at least one of N,N′-dinitrospentamethylenetetramine, azodicarbonamide, and 4,4′-oxodibenzenesulfonylhydrazine, preferably blowing agent 130A. Blowing agent 130A can be a white powder with a decomposition temperature of 130±3°C and an average particle size of 8–12 μm.

[0146] The specific formula example for foamed wear-resistant and anti-slip materials is as follows: In some embodiments, the raw materials of the wear-resistant and anti-slip material, by weight, include 30-50 parts of ethylene-vinyl acetate copolymer, 10-30 parts of random polyolefin elastomer, 10-20 parts of olefin block copolymer, 10-20 parts of ethylene-butyl acrylate copolymer, 5-15 parts of functional unit, 0.5-0.7 parts of peroxide crosslinking agent, 3-4 parts of foaming agent, 0.8-1.2 parts of zinc oxide, and 0.8-1.2 parts of stearic acid.

[0147] It should be noted that the wear-resistant and anti-slip material of this application can be used not only for foamed shoe soles, but also for tires, floor mats, anti-slip mats, conveyor belts, grips, and other polymer products that require both wear resistance and anti-slip properties. The polymer matrix can be a foamed material or a non-foamed material. When the polymer matrix is ​​a non-foamed material, a foaming agent may not be added, or a foaming step may not be performed.

[0148] The first wear-resistant particle is not limited to a specific grade of nano-silica; other nano-scale inorganic particles, organic particles, or organic-inorganic composite particles with a small wear volume and the ability to bond with the island phase matrix can also be used. The second wear-resistant particle is not limited to a specific grade of silicone microspheres; other micron-sized spherical particles or composite particles with a small wear volume can also be used.

[0149] The island phase matrix is ​​not limited to hydroxyl-terminated polydimethylsiloxane with a viscosity of 1500 cps; other hydroxyl-terminated polydimethylsiloxanes with viscosities of 1000–3000 cps can also be used. When the first and second wear-resistant particles can be bonded together and a stable interface can be formed with the marine phase, polymers with hydroxyl, siloxy, or other reactive groups can also be used as the island phase matrix.

[0150] The first anti-slip material is not limited to a specific grade of siloxy-functionalized styrene-ethylene / butene-styrene block copolymer, and the second anti-slip material is not limited to a specific grade of bi-terminated functionalized solution-polymerized styrene-butadiene rubber. As long as the coefficient of dynamic friction of the first anti-slip material in the first contact environment is greater than the coefficient of dynamic friction of the second anti-slip material and the polymer matrix, and the coefficient of dynamic friction of the second anti-slip material in the second contact environment is greater than the coefficient of dynamic friction of the first anti-slip material and the polymer matrix, other polymers or polymer composite materials can be selected according to the application environment.

[0151] The ethylene-vinyl acetate copolymer, random polyolefin elastomer, olefin block copolymer, and ethylene-butyl acrylate copolymer in the polymer matrix can be used alone or in different combinations. Antioxidants, pigments, fillers, foaming accelerators, crosslinking agents, lubricants, or other processing aids can also be added without hindering the formation and function of the functional units.

[0152] The technical effects of this application are further illustrated and demonstrated below through specific experimental data: The following is an example of a functional unit: Functional units 1-12 are prepared according to the aforementioned method, while functional units 13 and 14 are prepared according to the methods described below. Except for the types, amounts, and corresponding processing steps of raw materials that are explicitly changed or omitted in each sample, the remaining applicable preparation steps and process conditions remain the same. The total amount of raw materials listed in each sample is 100 parts by weight. Specifically, functional units 1-7 are used to illustrate the feasibility of different component ratios within the formulation range defined by the claims; functional units 8-12 omit one component from functional unit 4, and adjust the amount of EVA 28280 to maintain the total amount of raw materials in each functional unit at 100 parts by weight, to examine the effect of the omitted component on the performance of the functional unit; functional units 13 and 14 completely omit the island phase component and the first and second anti-slip bodies, respectively, to examine the effect of the complete island phase component and the complete anti-slip component on the material properties.

[0153] Functional unit 1 comprises 4 parts of nano-silicone spheres (SM), 8 parts of silicone microspheres, 12 parts of hydroxyl-terminated polydimethylsiloxane, 30 parts of siloxy-functionalized SEBS, 20 parts of dual-terminated solution-polymerized styrene-butadiene rubber, and 26 parts of EVA 28280. Functional unit 1 is used to describe the wear resistance, static dry slip resistance, and static wet slip resistance of the functional unit obtained when the wear-resistant component in the island phase and the anti-slip component in the marine phase are combined in the above proportions.

[0154] Based on Functional Unit 1, Functional Unit 2 adjusts the amount of nano-silicone spheres SM from 4 parts to 6 parts, the amount of silicone microspheres from 8 parts to 10 parts, the amount of hydroxyl-terminated polydimethylsiloxane from 12 parts to 15 parts, the amount of siloxy-functionalized SEBS from 30 parts to 20 parts, the amount of bi-terminated functionalized solution-polymerized styrene-butadiene rubber from 20 parts to 10 parts, and the amount of EVA 28280 to 39 parts.

[0155] Based on functional unit 1, functional unit 3 adjusts the amount of silicone microspheres from 8 parts to 6 parts, the amount of hydroxyl-terminated polydimethylsiloxane from 12 parts to 15 parts, and the amount of EVA 28280 from 26 parts to 25 parts; the types and amounts of the remaining components remain unchanged.

[0156] Based on Functional Unit 1, Functional Unit 4 adjusts the amount of nano-silicone spheres SM from 4 parts to 6 parts, the amount of silicone microspheres from 8 parts to 10 parts, the amount of hydroxyl-terminated polydimethylsiloxane from 12 parts to 15 parts, and the amount of EVA 28280 from 26 parts to 19 parts; the amount of siloxy-functionalized SEBS and bi-terminated solution-polymerized styrene-butadiene rubber remains unchanged.

[0157] Based on Functional Unit 1, Functional Unit 5 adjusts the amount of SM nanospheres from 4 parts to 6 parts, the amount of silicone microspheres from 8 parts to 6 parts, the amount of hydroxyl-terminated polydimethylsiloxane from 12 parts to 10 parts, and the amount of EVA 28280 from 26 parts to 28 parts; the amount of siloxy-functionalized SEBS and bi-terminated solution-polymerized styrene-butadiene rubber remains unchanged.

[0158] Based on functional unit 1, functional unit 6 adjusts the amount of siloxy-functionalized SEBS from 30 parts to 20 parts and the amount of bi-terminal functionalized solution-polymerized styrene-butadiene rubber from 20 parts to 30 parts; the types and amounts of the remaining components remain unchanged.

[0159] Based on functional unit 1, functional unit 7 adjusts the amount of siloxy-functionalized SEBS from 30 parts to 40 parts and the amount of bi-terminal functionalized solution-polymerized styrene-butadiene rubber from 20 parts to 10 parts; the types and amounts of the remaining components remain unchanged.

[0160] The amounts of nano-silicon spheres SM, silicone microspheres, hydroxyl-terminated polydimethylsiloxane, and EVA 28280 in functional units 6, 1, and 7 remain unchanged, and the total amount of siloxy-functionalized SEBS and bi-terminated solution-polymerized styrene-butadiene rubber is 50 parts each.

[0161] Functional unit 8 does not add nano-silicon spheres SM based on functional unit 4, and the amount of EVA 28280 is adjusted from 19 parts to 25 parts; the types and amounts of the remaining components remain unchanged.

[0162] Functional unit 9 does not add silicone microspheres to functional unit 4, and the amount of EVA 28280 is adjusted from 19 parts to 29 parts; the types and amounts of the remaining components remain unchanged.

[0163] Functional unit 10 does not add hydroxyl-terminated polydimethylsiloxane based on functional unit 4, and adjusts the amount of EVA28280 from 19 parts to 34 parts; the types and amounts of the remaining components remain unchanged.

[0164] Functional unit 11 does not add siloxy-functionalized SEBS based on functional unit 4, and the amount of EVA 28280 is adjusted from 19 parts to 49 parts; the types and amounts of the remaining components remain unchanged.

[0165] Functional unit 12 does not add dual-terminal functionalized solution polystyrene-butadiene rubber based on functional unit 4, and adjusts the amount of EVA28280 from 19 parts to 39 parts; the types and amounts of the remaining components remain unchanged.

[0166] Functional unit 13 is based on functional unit 4 without adding nano-silicon spheres SM, silicone microspheres, or hydroxyl-terminated polydimethylsiloxane, and the amount of EVA 28280 is adjusted from 19 parts to 50 parts; the types and amounts of the remaining components remain unchanged.

[0167] Functional unit 14 is based on functional unit 4 without adding siloxy-functionalized SEBS and dual-terminal functionalized solution-polymerized styrene-butadiene rubber, and the amount of EVA 28280 is adjusted from 19 parts to 69 parts; the types and amounts of the remaining components remain unchanged.

[0168] It should be noted that functional units 13 and 14 are comparative sample names used for the purpose of unifying numbering with other samples. Functional unit 13 does not contain silicon nanospheres, silicone microspheres, or hydroxyl-terminated polydimethylsiloxane, and therefore does not form the aforementioned island phase; functional unit 14 does not contain siloxy-functionalized SEBS or bi-terminated solution-polymerized styrene-butadiene rubber, and therefore cannot form an independent island phase within the EVA matrix. Functional units 13 and 14 are used to examine the influence of complete island phase components and complete anti-slip components on material properties, and do not imply that both possess all the technical features of the complete functional unit described in this application.

[0169] When preparing functional unit 13, the preparation step of island phase premix is ​​omitted. 30 parts of siloxy-functionalized SEBS, 20 parts of bi-terminal functionalized solution-polymerized styrene-butadiene rubber and 50 parts of EVA 28280 are mixed, melt-blended and granulated. Except for omitting the preparation step of island phase premix, the other corresponding processing conditions are the same as those of functional unit 4.

[0170] In preparing functional unit 14, 6 parts of nano-silicone spheres SM, 10 parts of silicone microspheres, and 15 parts of hydroxyl-terminated polydimethylsiloxane were first pre-processed to obtain an island-phase premix. The island-phase premix was then mixed, melt-blended, and granulated with 69 parts of EVA 28280. Except for the absence of siloxy-functionalized SEBS and bi-terminated solution-polymerized styrene-butadiene rubber, the processing conditions remained the same as for functional unit 4. When functional unit 14 was further compounded with an EVA-based polymer matrix, the EVA 28280 was mixed with the polymer matrix and could not form an independent island-phase distinct from the polymer matrix to support and surround the island phase. Therefore, the resulting material did not possess the complete island-phase structure functional unit described in this application.

[0171] The composition of functional units 1-14 is as follows Figure 3 As shown.

[0172] The specific parameters and manufacturers of each component are as follows: SM nano-silicon spheres: particle size 50-100nm, Nanjing Dongna Biotechnology Co., Ltd.

[0173] Silicone microspheres: particle size 8-10µm, Hangzhou Yuheng Technology Co., Ltd.

[0174] Hydroxyl-terminated polydimethylsiloxane: 1500 cps, Shenzhen Sicheng Silicone Co., Ltd.

[0175] Silicon-oxygen-functionalized SEBS: Hardness 78A, grafting rate 5%, styrene content 33%, tensile strength 19.8MPa, elongation at break 1110%, Kronentech.

[0176] Dual-terminated functionalized solution polystyrene-butadiene rubber: styrene content approximately 34.1%, vinyl content approximately 38.7%, Mooney viscosity approximately 40-55 (ML 1+4 @ 100℃), China National Petroleum Corporation.

[0177] EVA 28280: VA molar content is 28%, hardness is 73A, MI=28g / 10min, melting point is 67℃, tensile strength is 12MPa, elongation at break is 800%, Asia Polymer Co., Ltd.

[0178] Data Analysis: The formulation design and test data of functional units 1-7 show that adjusting the amounts of nano-silicone balls (4-6 parts), silicone microspheres (6-10 parts), hydroxyl-terminated polydimethylsiloxane (8-15 parts), siloxy-functionalized SEBS (20-40 parts), dual-terminated functionalized solution-polymerized styrene-butadiene rubber (10-30 parts), and ethylene-vinyl acetate eVA (15-40 parts) yields functional units with a DIN abrasion resistance ≤35mm³, static dry slip resistance ≥1.3, and static wet slip resistance ≥0.85. Furthermore, as the amounts of nano-silicone balls, silicone microspheres, and hydroxyl-terminated polydimethylsiloxane in the functional units gradually increase, the DIN abrasion resistance of the test piece improves (lower values ​​indicate better abrasion resistance), but the slip resistance decreases (lower values ​​indicate worse slip resistance). With the gradual increase in the amounts of siloxy-functionalized SEBS and dual-terminated functionalized solution-polymerized styrene-butadiene rubber, the static dry and wet slip resistance of the test piece improves, but the DIN abrasion resistance slightly decreases. When the amounts of nano-silicone spheres, silicone microspheres, and hydroxyl-terminated polydimethylsiloxane are fixed, and the total amount of siloxy-functionalized SEBS and bi-terminated solution-polymerized styrene-butadiene rubber remains unchanged, the greater the amount of siloxy-functionalized SEBS added, the better the static dry slip performance of the specimen; and the greater the amount of bi-terminated solution-polymerized styrene-butadiene rubber added, the better the static wet slip performance of the specimen.

[0179] The formulation design and test data of functional units 8-12 show that: if one of the following is not added: nano-silicone balls, silicone microspheres, or hydroxyl-terminated polydimethylsiloxane, the DIN abrasion resistance will decrease significantly, but the static dry and wet slip resistance will not change much; if siloxy-functionalized SEBS is not added, the static dry slip resistance will decrease significantly, the static wet slip resistance will decrease somewhat, but the DIN will not change much; if dual-terminated functionalized solution polystyrene-butadiene rubber is not added, the static wet slip resistance will decrease significantly, the static dry slip resistance will decrease somewhat, but the DIN abrasion resistance will not change much.

[0180] The formulation design and test data of functional units 13-14 show that if island phase components such as nano-silicone balls, silicone microspheres, and hydroxyl-terminated polydimethylsiloxane are not added at the same time, the wear resistance of DIN will drop sharply. Also, due to the increase in EVA addition, the static dry and wet anti-slip performance will also decrease. If siloxy-functionalized SEBS and dual-terminated solution-polymerized styrene-butadiene rubber are not added at the same time, the static dry and wet anti-slip performance will drop sharply, but the change in DIN wear resistance will not be significant.

[0181] Examples 1-11 below are all foaming examples obtained by adding corresponding functional units to polymer base materials and performing crosslinking and foaming. Except for the different types or amounts of functional units, the polymer base materials, crosslinking agents, foaming agents, stearic acid, zinc oxide, and preparation process conditions used in each example are kept the same. Each example includes 50 parts of EVA 26061, 20 parts of POE 8150, 15 parts of OBC 9107, 15 parts of EBA 3717, 0.6 parts of BIBP 14S-FL, 3.5 parts of foaming agent 130A, 1 part of stearic acid, and 1 part of ZnO 997.

[0182] Example 1: Based on the above common formula, 10 parts of functional unit 1 were added to examine the density, hardness, wear resistance, dry and wet anti-slip properties and compression properties of the wear-resistant and anti-slip material obtained after functional unit 1 was added to the polymer matrix and cross-linked and foamed.

[0183] Example 2 is based on Example 1, but 10 parts of functional unit 1 are replaced with 10 parts of functional unit 2, while the other raw materials and preparation conditions remain unchanged.

[0184] Example 3 is based on Example 1, but 10 parts of functional unit 1 are replaced with 10 parts of functional unit 3, while the other raw materials and preparation conditions remain unchanged.

[0185] Example 4 is based on Example 1, but 10 parts of functional unit 1 are replaced with 10 parts of functional unit 4, while the other raw materials and preparation conditions remain unchanged.

[0186] Example 5 is based on Example 1, but 10 parts of functional unit 1 are replaced with 10 parts of functional unit 5, while the other raw materials and preparation conditions remain unchanged.

[0187] Example 6 is based on Example 1, but 10 parts of functional unit 1 are replaced with 10 parts of functional unit 6, while the other raw materials and preparation conditions remain unchanged.

[0188] Example 7 is based on Example 1, but 10 parts of functional unit 1 are replaced with 10 parts of functional unit 7, while the other raw materials and preparation conditions remain unchanged.

[0189] In Example 8, based on Example 4, the amount of functional unit 4 added was reduced from 10 parts to 5 parts, while the other raw materials and preparation conditions remained unchanged.

[0190] In Example 9, based on Example 4, the amount of functional unit 4 added was increased from 10 parts to 15 parts, while the other raw materials and preparation conditions remained unchanged.

[0191] Example 10 is based on Example 5, but the amount of functional unit 5 added is reduced from 10 parts to 5 parts, while the other raw materials and preparation conditions remain unchanged.

[0192] In Example 11, based on Example 5, the amount of functional unit 5 added was increased from 10 parts to 15 parts, while the other raw materials and preparation conditions remained unchanged.

[0193] The polymer base, crosslinking agent, foaming agent, stearic acid, zinc oxide and preparation process conditions used in the following examples and comparative examples are the same as those in Example 4. The main difference lies in the composition of the functional units or the amount of functional units added.

[0194] Comparative Example 3 is based on Example 4, except that 10 parts of functional unit 4 are replaced with 10 parts of functional unit 8, while the other raw materials and preparation conditions remain unchanged.

[0195] Comparative Example 4 is based on Example 4, except that 10 parts of functional unit 4 are replaced with 10 parts of functional unit 9, while the other raw materials and preparation conditions remain unchanged.

[0196] Comparative Example 5 is based on Example 4, except that 10 parts of functional unit 4 are replaced with 10 parts of functional unit 10, while the other raw materials and preparation conditions remain unchanged.

[0197] Comparative Example 6 is based on Example 4, except that 10 parts of functional unit 4 are replaced with 10 parts of functional unit 11, while the other raw materials and preparation conditions remain unchanged.

[0198] Comparative Example 7 is based on Example 4, except that 10 parts of functional unit 4 are replaced with 10 parts of functional unit 12, while the other raw materials and preparation conditions remain unchanged.

[0199] In Example 12, based on Example 4, the amount of functional unit 4 added was increased from 10 parts to 20 parts, while the other raw materials and preparation conditions remained unchanged.

[0200] Comparative Example 1 is based on Example 4, except that 10 parts of functional unit 4 are replaced with 10 parts of ordinary silicone wear-resistant agent, while the other raw materials and preparation conditions remain unchanged.

[0201] Comparative Example 2 is based on Example 8, except that 5 parts of functional unit 4 are replaced with 5 parts of ordinary silicone wear-resistant agent, while the other raw materials and preparation conditions remain unchanged.

[0202] Comparative Example 8 is based on Example 4, except that 10 parts of functional unit 4 are replaced with 10 parts of functional unit 13, while the other raw materials and preparation conditions remain unchanged.

[0203] Comparative Example 9 is based on Example 4, except that 10 parts of functional unit 4 are replaced with 10 parts of functional unit 14, while the other raw materials and preparation conditions remain unchanged.

[0204] The composition of each embodiment and comparative example is as follows: Figure 4 and Figure 5 As shown.

[0205] in: EVA 26061: VA molar content is 26%, hardness is 80A, MI=5.5g / 10min, melting point is 71℃, tensile strength is 20MPa, elongation at break is 780%, Asia Polymer Co., Ltd.

[0206] POE 8150: Hardness 70A, melting point 55℃, MI=0.5g / 10min, tensile strength 9.5MPa, elongation at break 600%, Dow Chemical Company, USA.

[0207] OBC 9107: Hardness 60A, melting point 121℃, MI=1.0g / 10min, tensile strength 5.1MPa, elongation at break 600%, Dow Chemical Company, USA.

[0208] EBA3717: 17% acrylate content, hardness 89A, melting point 96℃, MI=7.0g / 10min, tensile strength 40MPa, DuPont, USA.

[0209] Functional unit: Self-made.

[0210] Silicone abrasion resistant agent: white granules, 90% ultra-high molecular weight silicone + 10% EVA resin, DIN abrasion resistance of test piece 52, static dry slip 0.78, static wet slip 0.32, Xiamen Baishiyuan Industry & Trade Co., Ltd.

[0211] BIBP 14S-FL: White granules, melting point 46-52℃, AkzoNobel.

[0212] Foaming agent 130A: White powder, decomposition temperature 130±3℃, average particle size 8-12um, Fujian Jinlang New Material Technology Co., Ltd.

[0213] ZnO 997: White powder, Shipai zinc oxide, with a relative density of 4.42~4.45.

[0214] Stearic acid: white granules, from Dukuda, Indonesia.

[0215] Implementation steps: This application applies to IP process (injection molding foam molding process) and MD process (compression molding foam molding process).

[0216] (1) Preparation of functional units Weigh out 4-6 parts of nano-silica spheres, 6-10 parts of silicone microspheres, and 8-15 parts of hydroxyl-terminated polydimethylsiloxane, and pour them into a high-speed mixer. Mix for 20-30 minutes at a stirring speed of 800-1500 rpm and a mixing temperature of 40-50℃. Then add 20-40 parts of siloxy-functionalized SEBS, 10-30 parts of dual-terminated functionalized solution-polymerized styrene-butadiene rubber, and 15-40 parts of ethylene-vinyl acetate (EVA) and mix for 10-20 minutes at a stirring speed of 1000-1500 rpm and a mixing temperature of 60-80℃ to obtain blend 1. Blend 1 is modified, extruded, and granulated using a twin-screw granulator at a processing temperature of 120±5℃ to obtain island-structured functional units.

[0217] (2) IP process implementation steps: Implementation steps: ① Weighing: Based on the dosage of the formula, weigh BIBP, foaming agent, stearic acid, and zinc oxide as the first group; weigh the remaining materials as the second group.

[0218] ② Mixing: First, pour the second batch of materials into the internal mixer and turn on the machine. Wait for the temperature to rise to between 95-105℃; then pour in the first batch of materials; when the temperature rises to 105-115℃, pour out the mixed materials.

[0219] ③ Granulation: Pour the mixed material into the pellet mill. Adjust the temperatures of the first, second, third, and fourth zones to 95, 100, 105, and 110℃ respectively. Adjust the screw speed to 55-60 rpm and the cutting speed to 20-25 rpm.

[0220] Foaming: Pour the prepared material into the injection molding foaming machine. Adjust the temperatures of the first, second, third, and fourth feeding zones to 95, 100, 105, and 110℃ respectively. Adjust the temperatures of the upper and lower mold plates to 173±5℃ and 173±5℃ respectively. Set the material quantity according to the shoe sole mold requirements (based on a foaming ratio of 190%, the material quantity can be set to 80±10g), the injection time to 220±20 seconds, and the vulcanization foaming time to 550±30 seconds.

[0221] Baking: Set the temperatures of the first, second, third, and fourth zones of the oven to 70, 80, 90, and 100℃ respectively, and the rotation speed to 60-70 rpm. Place the foamed material into the oven opening. The oven length should be 30 meters. The baking time from start to finish should be 25-30 minutes.

[0222] (3) MD process implementation steps: Implementation steps: The processes of weighing, mixing, and granulation are consistent with those of IP processes ①, ②, and ③.

[0223] Small foaming: Pour the prepared granules into a flat mold for small foaming to complete the first foaming. The foaming temperature is 173±5℃ and the foaming time is 530±30 seconds.

[0224] Compression molding: After the semi-finished product with small foam has been left to stand and cool for 12-24 hours, press the semi-finished product into a flat molding die to complete the molding of the finished product; the hot pressing temperature is 173±3℃; the hot pressing time is 500±30 seconds; the cooling water temperature is <25℃ and the cooling time is 500±30 seconds.

[0225] Mechanical property data for each embodiment and comparative example are as follows: Figure 6 and Figure 7 As shown.

[0226] In the table, the codes following each test method represent the corresponding standard or test method number. "GB / T" indicates a national recommended standard of the People's Republic of China; "DIN" indicates a standard published or adopted by the German Institute for Standardization; "ASTM" indicates a standard published by ASTM International; and "SATRA™" indicates a test method developed by SATRA. Unless otherwise stated, all examples and comparative examples use the same sample preparation method, testing equipment, testing conditions, and data processing methods for the same test item to ensure comparability of the corresponding test results. The standard or test method numbers listed in the table are based on the actual standard version and original test report used during the testing.

[0227] Specifically, the DIN abrasion test is used to characterize the volume loss of a sample under specified abrasion conditions; the national standard abrasion mark test is used to characterize the length of the abrasion mark after the whole shoe or sole material has undergone specified abrasion; the static dry slip, static wet slip, dynamic dry slip and dynamic wet slip tests are used to characterize the friction performance of a sample under corresponding dry or wet contact environments; and the compression deformation test is used to characterize the degree to which a sample retains its deformation after being subjected to specified compression.

[0228] in conclusion: The test data from Examples 1-11 show that when the following components are fixed: 50 parts EVA, 20 parts POE, 15 parts OBC, 15 parts ethylene-butyl acrylate copolymer (EBA), 5-15 parts functional units, 0.6 parts peroxide crosslinking agent, 3.5 parts foaming agent, 1.0 part zinc oxide, and 1.0 part stearic acid, a foamed shoe sole with static dry slip ≥1.1, static wet slip ≥0.75, dynamic dry slip ≥0.95, dynamic wet slip ≥0.5, national standard abrasion mark ≤9.5mm, DIN abrasion resistance ≤100mm3, and compression deformation ≤35% can be obtained. Its abrasion resistance and anti-slip performance achieve a good balance, fully meeting the abrasion resistance and anti-slip requirements when the EVA midsole is in direct contact with the ground.

[0229] The test data from Examples 4 / 8 / 9, 12, 5 / 10 / 11 show that as the amount of functional unit 4 / 5 added increases, the DIN abrasion resistance and national standard abrasion marks of the foamed sole gradually decrease (the smaller the value, the better the abrasion resistance). However, the static dry / wet slip and dynamic / static dry / wet slip deteriorate. When the amount added reaches 20 parts (Example 12), although the abrasion resistance is very good, the anti-slip performance decreases too much. Therefore, the preferred amount of functional unit added is 5-15 parts.

[0230] The test data from Example 4 and Comparative Example 3 show that when nano-silica balls are not used in the functional unit, the DIN abrasion resistance and national standard abrasion mark performance of the final foamed sole decreases significantly, but the change in anti-slip performance is relatively small. This indicates that the nanoscale size of the nano-silica balls endows them with a significant quantum size effect and high specific surface area, and the nano-island phase formed in the foamed sole can enhance the abrasion resistance of the foamed sole.

[0231] The test data from Example 4 and Comparative Example 4 show that when silicone microspheres are not used in the functional unit, the DIN abrasion resistance and national standard abrasion mark performance of the final foamed sole decreases significantly, but the change in anti-slip performance is relatively small. This indicates that although the particle diameter of silicone microspheres is on the micrometer scale, they have a three-dimensional cross-linked network molecular structure and contain organic functional groups, which allows them to have good compatibility with other polymers in the foam matrix. Simultaneously, they enhance the strength of hydroxyl-terminated polydimethylsiloxane, and the micrometer-sized island phase formed in the foamed sole can enhance its abrasion resistance.

[0232] The test data from Example 4 and Comparative Example 5 show that when hydroxyl-terminated polydimethylsiloxane is not used in the functional unit, the DIN abrasion resistance and national standard abrasion mark performance of the final foamed shoe sole decreases significantly, while the anti-slip performance changes little. This indicates that the highly reactive hydroxyl-terminated polydimethylsiloxane has hydroxyl functional groups at both ends that can react with siloxy-functionalized SEBS and bi-terminated solution-polymerized styrene-butadiene rubber. Furthermore, the terminal hydroxyl groups undergo condensation reactions with the hydroxyl groups on the surface of the nano-silicon spheres to form stable Si-O-Si covalent bonds. Through the physical adsorption of the molecular chains, these bonds encapsulate the surface of SiO2 particles, which is beneficial for enhancing the interfacial bonding force between the marine and island phases of the functional unit.

[0233] The test data from Example 4 and Comparative Example 6 show that when siloxy-functionalized SEBS is not used in the functional unit, the static dry / dynamic dry slip performance of the final foamed sole decreases significantly, the static / dynamic wet slip performance decreases somewhat, and the DIN abrasion resistance and national standard abrasion mark performance decrease slightly. This indicates that the siloxy-functionalization in siloxy-functionalized SEBS can act as a reaction site, improving interfacial bonding through covalent or hydrogen bonding. It not only acts as a compatibilizer, improving the dispersion of nano-silica in the polymer matrix and enhancing the mechanical properties of the composite material, but also optimizes the frictional characteristics of the material surface and contact surface, significantly improving its dry slip performance.

[0234] The test data from Example 4 and Comparative Example 7 show that when the functional unit does not use dual-terminal functionalized solution-polymerized styrene-butadiene rubber (SBR), the static / dynamic wet slip performance of the final foamed sole decreases significantly, the static / dynamic dry slip performance decreases somewhat, and the DIN abrasion resistance and national standard abrasion mark performance decrease slightly. This indicates that the dual-terminal functionalization design creates interfacial interaction sites at both ends of the SBR molecules, enhancing the bonding force with the nano-silicon spheres. Compared to non-functionalized products, the polar functional groups (terminal amino groups and terminal siloxane groups) introduced at both ends of the SBR molecular chain rapidly adsorb water molecules through hydrogen bonding in a wet road environment, forming a dynamic hydrophilic interfacial layer. This interfacial layer can disrupt the water film between the sole and the road surface, increasing the microscopic contact area, thereby improving the coefficient of friction under wet slip conditions and enhancing the anti-slip performance.

[0235] The test data from Examples 4 / 8 and Comparative Examples 1 / 2 show that when using ordinary silicone abrasion-resistant agents, at the same addition amount, the effect of ordinary silicone abrasion-resistant agents on improving abrasion resistance is not as good as that of the island-structure functional unit of this application. Its DIN abrasion resistance is >100mm³, national standard abrasion mark is >10mm, and compression deformation is >35%. Furthermore, when the addition reaches 5 parts, the static dry and wet slip / dynamic dry and wet slip performance of the foamed sole is already very poor, and the compression deformation performance also decreases significantly, failing to meet the ground contact requirements of sports shoe soles. This indicates that this application, by preparing island-structure functional units, effectively improves the abrasion resistance of EVA-based foamed soles and balances anti-slip performance and compression performance.

[0236] The test data from Example 4 and Comparative Example 8 show that when island phase components such as nano-silicon spheres, silicone microspheres, and hydroxyl-terminated polydimethylsiloxane are not used in the functional unit, the DIN abrasion resistance and national standard abrasion performance of the final foamed shoe sole are significantly reduced, indicating the beneficial effect of island phase abrasion-resistant components on the abrasion resistance of the foamed shoe sole.

[0237] The test data from Example 4 and Comparative Example 9 show that when the functional unit does not use siloxy-functionalized SEBS or dual-terminated functionalized solution-polymerized styrene-butadiene rubber, and does not form an independent marine phase, the static dry-slip and dynamic dry-slip properties of the final foamed sole both decrease significantly, and the DIN abrasion resistance and national standard abrasion mark resistance also decrease. This demonstrates the beneficial effect of the marine phase anti-slip component on the anti-slip performance of the foamed sole.

[0238] It should be noted that the order of description of the embodiments in this application is not intended to limit the priority of the embodiments.

[0239] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in this application and in its specification is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.

[0240] The embodiments of this application have been described above with reference to the accompanying drawings. However, this application is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many forms under the guidance of this application without departing from the spirit and scope of protection of the claims. All equivalent transformations made under the inventive concept of this application using the content of this application's specification and drawings, or direct / indirect applications in other related technical fields, are included within the patent protection scope of this application.

Claims

1. A wear-resistant and anti-slip material, characterized in that, It includes a polymer matrix and multiple functional units dispersed in the polymer matrix; The functional unit has an island structure and includes marine facies and island facies dispersed in the marine facies; The wear volume of the island phase is smaller than that of the marine phase and the polymer matrix, and the dynamic friction coefficient of the marine phase is greater than that of the island phase and the polymer matrix. in, The island phase is prepared from raw materials comprising the following components in parts by weight: 4 to 6 parts of silica particles, 6 to 10 parts of silicone particles and 8 to 15 parts of hydroxyl-terminated polydimethylsiloxane. The marine phase is prepared from raw materials comprising the following components in parts by weight: 20-40 parts of siloxy-functionalized styrene-ethylene / butene-styrene block copolymer, 10-30 parts of bi-terminated functionalized solution-polymerized styrene-butadiene rubber, and 15-40 parts of ethylene-vinyl acetate copolymer.

2. The wear-resistant and anti-slip material according to claim 1, characterized in that, The size of the silica particles is in the nanometer range.

3. The wear-resistant and anti-slip material according to claim 2, characterized in that, The average particle size of the silica particles is 10–100 nm.

4. The wear-resistant and anti-slip material according to claim 1, characterized in that, The silicone particles are in the micrometer range in size.

5. The wear-resistant and anti-slip material according to claim 4, characterized in that, The average particle size of the silicone particles is 5–10 μm.

6. The wear-resistant and anti-slip material according to claim 1, characterized in that, The silicone particles and the silicon dioxide particles are spherical particles.

7. The wear-resistant and anti-slip material according to claim 1, characterized in that, The polymer matrix has multiple pores formed within it; the polymer matrix includes one or more of ethylene-vinyl acetate copolymer, random polyolefin elastomer, olefin block copolymer, and ethylene-butyl acrylate copolymer.

8. The wear-resistant and anti-slip material according to claim 1, characterized in that, Based on the weight parts of each raw material used to prepare the functional unit, the island phase comprises 6 parts of spherical nano-silica, 10 parts of silicone microspheres and 15 parts of hydroxyl-terminated polydimethylsiloxane, and the marine phase comprises 30 parts of siloxy-functionalized styrene-ethylene / butene-styrene block copolymer, 20 parts of bi-terminated functionalized solution-polymerized styrene-butadiene rubber and 19 parts of ethylene-vinyl acetate copolymer.

9. A method for preparing the wear-resistant and anti-slip material according to any one of claims 1-8, characterized in that, include: Prepare a functional unit, the functional unit comprising a marine facies and island facies dispersed in the marine facies; The functional units are mixed with the polymer base material, so that the multiple functional units are dispersed in the polymer matrix formed by the polymer base material to obtain the wear-resistant and anti-slip material. Under the same test conditions, the wear volume of the island phase is smaller than that of the marine phase and the polymer matrix, and the dynamic friction coefficient of the marine phase is greater than that of the island phase and the polymer matrix.

10. The method according to claim 9, characterized in that, The preparation functional unit includes: Preprocessing silica particles, silicone particles, and hydroxyl-terminated polydimethylsiloxane to distribute the silica particles and silicone particles in the hydroxyl-terminated polydimethylsiloxane and bind them together through the hydroxyl-terminated polydimethylsiloxane, yields an island-phase premix. The island phase premix is ​​successively melt-blended and granulated with the siloxy-functionalized styrene-ethylene / butene-styrene block copolymer, the bi-terminated functionalized solution-polymerized styrene-butadiene rubber, and the ethylene-vinyl acetate copolymer, so that the siloxy-functionalized styrene-ethylene / butene-styrene block copolymer, the bi-terminated functionalized solution-polymerized styrene-butadiene rubber, and the ethylene-vinyl acetate copolymer form the marine phase, and the island phase formed by the island phase premix is ​​dispersed in the marine phase to obtain the functional unit.

11. The method according to claim 9 or 10, characterized in that, The process of mixing the functional unit with the polymer base material includes: pre-mixing the functional unit with the polymer base material, adding a crosslinking agent and a foaming agent after mixing, and then performing crosslinking and foaming to form multiple pores in the polymer matrix.